THE ESSENCE OF THE ENGLISH LANGUAGE AND ITS ROLE IN MODERN SOCIETY - Tojiyeva Marxabo Akbarovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article analyzes the role of the English language in the modern world, emphasizing its essence not merely as a tool for communication, but as the main driving force of global integration, science, technology, and business. It highlights the historical development stages of the language and the reasons for its rise to the status of a "lingua franca" (universal language of communication). Furthermore, the positive impact of learning English on personal and professional development is demonstrated.